2010
DOI: 10.4103/0301-4738.71678
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and antibacterial susceptibility pattern of community-acquired bacterial ocular infections in a tertiary eye care hospital in south India

Abstract: Aims:To identify the etiology, incidence and prevalence of ocular bacterial infections, and to assess the in vitro susceptibility of these ocular bacterial isolates to commonly used antibiotics.Materials and Methods:Retrospective analysis of consecutive samples submitted for microbiological evaluation from patients who were clinically diagnosed with ocular infections and were treated at a tertiary eye care referral center in South India between January 2002 and December 2007.Results:A total of 4417 ocular samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
74
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 20 publications
28
74
1
4
Order By: Relevance
“…The predominant bacterial isolates were S. aureus (21.0%) followed by CoNS (18.2%) and S. pneumoniae (14.0%). This finding is in agreement with previous works elsewhere (Modarrres et al, 1998;Nigatu, 2004;Ubani, 2009;Bharathi et al, 2010 andAnagaw et al, 2011). However, in other studies by Dagnachew et al (2014) and Summaiya et al (2012), the predominant isolates were CoNS.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The predominant bacterial isolates were S. aureus (21.0%) followed by CoNS (18.2%) and S. pneumoniae (14.0%). This finding is in agreement with previous works elsewhere (Modarrres et al, 1998;Nigatu, 2004;Ubani, 2009;Bharathi et al, 2010 andAnagaw et al, 2011). However, in other studies by Dagnachew et al (2014) and Summaiya et al (2012), the predominant isolates were CoNS.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, Gram positive cocci are still the most common isolates (61.5%). Several other studies in Ethiopia (Nigatu, 2004;Anagaw et al, 2011;Tewelde et al, 2013 andDagnachew et al, 2014); in India (Sherwal and Verma, 2008;Bharathi et al, 2010;and Ramesh et al, 2010), in Nigeria (Ubani, 2009); in USA (Adebukola et al, 2011) and other parts of world have shown similar results inferring Gram positive cocci as a primary cause of bacterial ocular infection. The predominant bacterial isolates were S. aureus (21.0%) followed by CoNS (18.2%) and S. pneumoniae (14.0%).…”
Section: Discussionsupporting
confidence: 57%
“…16,[30][31][32][33] Environmental organisms were recovered in all but one of the culturepositive corneal samples and, although these numbers are low, this finding would be consistent with higher recovery of environmental causative organisms in tropical climate zones. 15 P. aeruginosa is a common environmental pathogen that is able to survive in contact lens storage cases.…”
Section: Discussionsupporting
confidence: 64%
“…The resistance of Pseudomonas to disinfectants, coupled with its adherence capability to plastics, facilitates its introduction into the eye where it can react with defective corneal epithelium, gaining further entrance into the corneal stroma. S. pneumonia on the other hand is the major cause of corneal ulcers in developing countries however, some reports emphasize on the fact that Streptococcus are most commonly encountered after P. aeruginosa and/or S. aureus eye infections [14,114,215]. Unlike P. aeruginosa, pneumococcal keratitis is not commonly associated with the use of contact lenses and the predisposing factors often include ocular trauma or surgery [31,104,114,125,160,207].…”
Section: Bacterial Keratitismentioning
confidence: 99%